Lupus in elderly: An observational study - Alakes Kumar Kole; Shalini Halder (Annals of Medical Science and Research)
Introduction: Lupus is an autoimmune disease with multisystem involvement. The disease may be seen in the elderly, and due to nonspecific presentation in this age group, only a high degree of suspicion helps diagnose cases. Moreover, in the presence of several comorbidities in the elderly, the management of lupus often becomes difficult and challenging, resulting in increased morbidity and mortality. Aims and Objectives: To evaluate the presentation, organ damage, and outcomes of lupus in elderly patients. Materials and Methods: About 50 (n = 50) lupus patients above 50 years of age were evaluated with respect to their presentation, organ damage, and outcomes. Results: The female-to-male ratio was 2.8:1, and the majority of them had nonspecific presentations such as fatigue, weakness, weight loss, and low-grade fever. The musculoskeletal system was seen most commonly involved, followed by cutaneous and neurological involvement. These patients had several comorbidities such as diabetes, hypertension, and dyslipidemia in various combinations, and all these, besides lupus, contributed to increased morbidity and mortality in comparison to lupus in the younger. Conclusions: Lupus in the elderly needs a strong suspicion, and the presence of comorbidities in addition to organ damage by the disease itself really makes a challenge for the treating physician.